2012
DOI: 10.1002/tax.613005
|View full text |Cite
|
Sign up to set email alerts
|

A plastid DNA phylogeny ofDasymaschalon(Annonaceae) and allied genera: Evidence for generic non–monophyly and the parallel evolutionary loss of inner petals

Abstract: Dasymaschalon and the closely related genera Desmos, Friesodielsia and Monanthotaxis together comprise ca. 170 species of trees, shrubs and woody climbers distributed in tropical Africa and tropical Asia. These genera form the desmoid clade, which, because of the presence of diverse flower and fruit syndromes including different types of pollination chambers and moniliform monocarps, offers an opportunity to investigate potentially ecologically significant shifts in flower and fruit characters. Despite its mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…We also find strong support that moniliform fruits (long strings of bead‐like fruitlets, found in e.g., extant Dasymaschalon , Desmos and Monanthotaxis , Guo, Hoekstra, et al., ; Wang et al., , Figures a and j), dehiscent fruits (e.g., found in extant Xylopia and Cymbopetalum , Figures j and i), and (relatively) small seeds (Figure c) are traits associated with long‐distance dispersal. Both moniliform and dehiscent fruits have been shown to be particularly attractive to birds (Gautier‐Hion et al., ; Guo, Hoekstra, et al., ; Lomáscolo & Schaefer, ), although Xylopia has been observed to be fed on by both birds and primates (Johnson & Murray, ).…”
Section: Discussionsupporting
confidence: 71%
“…We also find strong support that moniliform fruits (long strings of bead‐like fruitlets, found in e.g., extant Dasymaschalon , Desmos and Monanthotaxis , Guo, Hoekstra, et al., ; Wang et al., , Figures a and j), dehiscent fruits (e.g., found in extant Xylopia and Cymbopetalum , Figures j and i), and (relatively) small seeds (Figure c) are traits associated with long‐distance dispersal. Both moniliform and dehiscent fruits have been shown to be particularly attractive to birds (Gautier‐Hion et al., ; Guo, Hoekstra, et al., ; Lomáscolo & Schaefer, ), although Xylopia has been observed to be fed on by both birds and primates (Johnson & Murray, ).…”
Section: Discussionsupporting
confidence: 71%
“…with two other genera, Desmos and Monanthotaxis. This close relationship is corroborated by several diagnostic characters, including the glaucous abaxial surface of the leaves (Wang & al., 2012), inaperturate pollen with echinate-microbaculate ornamentation (Walker, 1971a; Le Thomas, 1980Thomas, , 1981Bygrave, 2000;Doyle & Le Thomas, 2012), and monocarps (when multi-seeded) with distinct constrictions between neighbouring seeds (Wang & al., 2012). As is generally the case in Annonaceae, however, these characters show homoplasies or reversals and therefore are not found in all species in the Dasymaschalon alliance.…”
Section: Introductionmentioning
confidence: 56%
“…Taxon and DNA region sampling. -The 42-taxon dataset generated by Wang & al. (2012) was used as the basis for an expanded taxon sampling, including additional species from the Dasymaschalon alliance, with a focus on Friesodielsia and Monanthotaxis, which were inadequately sampled previously (6 out of 49 Friesodielsia species, and 7 out of 66 Monanthotaxis species).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Popowia only differed from Monanthotaxis by having the petals in two whorls, however species of Enneastemon have the petals intermediate between Popowia and Monanthotaxis , which is a single whorl at the base of the flower, and in two whorls apically. With the rise of molecular phylogenetic analyses it has appeared that the genus Friesodielsia is polyphyletic, with most of the African species being sister to the genus Monanthotaxis (Chatrou et al 2012; Richardson et al 2004; Wang et al 2012). Further data sampling has also revealed that the monotypic genus Exellia is nested in Monanthotaxis .…”
Section: Introductionmentioning
confidence: 99%